ANALISIS KETIMPANGAN PEMBANGUNAN DI PROVINSI BENGKULU (TELAAH POSISI 3 KABUPATEN INDUK) - Novi Tri Putri; Aris Almahmudi (Universitas Bengkulu, 2020)
This research aim was to analized the development disparities in Bengkulu Province, and the position change of 3 parent districts. The analysis method used descriptive anylisis with Klassen Typology and Williamson Index (WI), and used data from BPS Bengkulu Province publication (2002-2016). The result show WI for 2002, 2007 and 2016 in a row amount to 0,34; 0,40 and 0,37; which mean that the area expantion may cause the development disparities more equal or not. In the years of observation, position of 3 parent disticts always changing in the regional stucture of Bengkulu Province. It may caused of the dinamic development of the district, both parent and new districts. Keywords : Development Disparities 1, Area Expansion 2, Klassen Typology 3, Williamson Index 4